2020
DOI: 10.1002/adfm.202002513
|View full text |Cite
|
Sign up to set email alerts
|

High Curie Temperature Ferromagnetism and High Hole Mobility in Tensile Strained Mn‐Doped SiGe Thin Films

Abstract: Diluted magnetic semiconductors based on group‐IV materials are desirable for spintronic devices compatible with current silicon technology. In this work, amorphous Mn‐doped SiGe thin films are first fabricated on Ge substrates by radio frequency magnetron sputtering and then crystallized by rapid thermal annealing (RTA). After the RTA, the samples become ferromagnetic semiconductors, in which the Curie temperature increases with increasing Mn doping concentration and reaches 280 K with 5% Mn concentration. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
(64 reference statements)
0
14
2
1
Order By: Relevance
“…The Mn 2p peaks are distributed around 641.89 eV and 652.73 eV, corresponding to Mn 2+ state. 20 Notably, the binding energies of Ge 0 and Ge 4+ states (28.92 eV and 32.84 eV), and Mn 0 , Mn 3+ and Mn 4+ states (638.45 eV, 640.46 eV and 642.23 eV) 30,35–37 are not observed in our samples. The results indicate that GeMnSe compounds are successfully synthesized and substitutional Mn 2+ ions are doped in the GeSe lattice.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The Mn 2p peaks are distributed around 641.89 eV and 652.73 eV, corresponding to Mn 2+ state. 20 Notably, the binding energies of Ge 0 and Ge 4+ states (28.92 eV and 32.84 eV), and Mn 0 , Mn 3+ and Mn 4+ states (638.45 eV, 640.46 eV and 642.23 eV) 30,35–37 are not observed in our samples. The results indicate that GeMnSe compounds are successfully synthesized and substitutional Mn 2+ ions are doped in the GeSe lattice.…”
Section: Resultscontrasting
confidence: 56%
“…27,28 The two peaks are blue-shifted with increasing the Mn concentration, owing to the increase of lattice constant caused by incorporation of Mn dopants with an atomic radius (1.61 Å) larger than that of Ge in the GeSe lattice. 29,30 Another small peak at 175.2 cm −1 exists in all the samples, which is corresponding to the A g 2 vibrational mode related to V Ge s in GeSe. 31 In addition, the peak at 258.7 cm −1 , which is attributed to the phonon vibrations of V Ge -induced Se chains and Ge–Se bonds, 32–34 dramatically decreases or even disappears after Mn doping, indicating that V Ge s are mainly occupied by Mn dopants.…”
Section: Resultsmentioning
confidence: 89%
“…Итоговый, впервые в полном объеме представленный результат относится к области физики спонтанного примесного магнетизма полупроводниковых кристаллов. Известные исследования в этой области сосредоточены на реализации магнитного упорядочения при достаточно высокой концентрации 3d-примесей ∼ (3−9) at.% и основаны на представлении о том, что спонтанная спиновая поляризация примесной электронной системы возникает благодаря межпримесному взаимодействию, которое обеспечивает взаимную спонтанную поляризацию ионных остовов примесных атомов [1][2][3].…”
Section: Introductionunclassified
“…Magnetic properties induced by vacancy defects, substitution doping, adsorption, edge effects, applied strain, and electric field in 2D materials have been extensively studied. In particular, the use of transition-metal atom (TM)-doped semiconductor is at a fairly mature stage, both theoretically and experimentally. Here, TMs serve as a source of spin or free charge in nonmagnetic semiconductors. For example, studies have shown that TM-doped 2D materials such as graphene, phosphorene, MoS 2 , and In 2 Se 3 monolayers provide valuable information on the properties of diluted magnetic semiconductors. The Mn-atom-doped SiGe thin film is successfully prepared and shows high T C (280 K) and high hole mobility (1003 cm 2 /(V s)) …”
Section: Introductionmentioning
confidence: 99%
“…24−33 The Mn-atom-doped SiGe thin film is successfully prepared and shows high T C (280 K) and high hole mobility (1003 cm 2 /(V s)). 34 The g-GeC monolayer is an important group IV binary compound that is widely used in heterostructure devices and solar cells due to its narrow optical band gap. 11 It is reported that g-GeC has a stable 2D honeycomb structure and a direct band gap.…”
Section: ■ Introductionmentioning
confidence: 99%